Circulating MicroRNA Expression Levels Associated With Internet Gaming Disorder - Lee, Minho; Cho, Hyeyoung; Jung, Seung Hyun; Yim, Seon-Hee; Cho, Sung-Min; Chun, Ji-Won; Paik, Soo-Hyun; Park, Yae Eun; Cheon, Dong Huey; Lee, Ji Eun; Choi, Jung-Seok; Kim, Dai-Jin; et al. (Frontiers in Psychiatry, 2018)
Background: Addictive use of the Internet and online games is a potential psychiatric disorder termed Internet gaming disorder (IGD). Altered microRNA (miRNA) expression profiles have been reported in blood and brain tissue of patients with certain psychiatric disorders and suggested as biomarkers. However, there have been no reports on blood miRNA profiles in IGD. Methods: To discover IGD-associated miRNAs, we analyzed the miRNA expression profiles of 51 samples (25 IGD and 26 controls) using the TaqMan Low Density miRNA Array. For validation, we performed qRT-PCR with 36 independent samples (20 IGD and 16 controls). Results: Through discovery and independent validation, we identified three miRNAs (hsa-miR-200c-3p, hsa-miR-26b-5p, hsa-miR-652-3p) that were significantly down-regulated in the IGD group. Individuals with all three miRNA alterations had a much higher risk of IGD than those with no alteration (Odds Ratio [OR] 22, 95% CI 2.29-211.11), and the ORs increased dose-dependently with number of altered miRNAs. The predicted target genes of the three miRNAs were associated with neural pathways. We explored the protein expression of the three downstream target genes by western blot and confirmed that expression of GABRB2 and DPYSL2 was significantly higher in the IGD group. Conclusions: We observed that expressions of hsa-miR-200c-3p, hsa-miR-26b-5p, and hsa-miR-652-3p were down-regulated in the IGD patients. Our results will be helpful to understand the pathophysiology of IGD.